TEACHING READING COMPREHENSION FOR THE TENTH GRADE STUDENTS BY APPLYING THE INQUIRY BASED LEARNING APPROACH - Maria Ramasari (Jurnal Perspektif Pendidikan, 2020)
The objective of this research was to find out whether or not it was significantly effective to apply the Inquiry Based Learning Approach in teaching reading comprehension for the tenth grade students. In this research, the researcher proposed two hypotheses. They were null hypothesis (Ho) and alternative hypothesis (Ha). The method applied was pre-experimental with one group pre-test posttest design. The object of this research consisted of 20 students. The data were collected by means of test consisting 20 items of multiple choices. The data obtained were analyzed through three techniques: 1) Individual Score, 2) Conversion of Individual Score Based on Minimum Mastery Criteria, and 3) Matched t-test. The results of this research shows that the students’ mean score in the pre-test was 60.13 and those in the post-test was 75.25. The result of matched t-test was 5.25, which was higher than t-table value (1.725) of 20 with 95% significant level for one tailed-test. Therefore, the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. It means that it was significantly effective in teaching reading to the tenth grade students by applying Based Learning Approach.